The Problem of Representation and Ethical Imagination: Case Study of Son of Saul - Sabolius, Kristupas (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English]The Son of Saul (2015), an award-winning film by László Nemes, can be interpreted as an exceptional case in film philosophy, which proposes a specific take on the interconnection between visual and ethical realms. This article reconstructs the premises of long-lasting polemics on the representability of Holocaust, simultaneously placing the case of Son of Saul in a more specific context on the debates concerning the meaning of four photos from Auschwitz taken by members of the Sonderkommando. László Nemes’s work cinematographically engages in these polemics and creates an opportunity to trace down different regimes of representation, as well as to highlight of ethical dimension of technomedia. By combining George Didi-Huberman’s ideas and Pietro Montani’s theory of intermedial imagination, the film can be regarded as a “middle ground” position in the given polemics, as it not only posits the need to “imagine in order to know”, but also employs a cinematographic strategy for performing an aesthetic and ethical revision.
Keywords: representation; ethics; imagination; Holocaust; visuality